Deleuze and the schizoanalysis of visual art - Buchanan, Ian, 1969-; Collins, Lorna, 1981- (Schizoanalytic applications., 2014)
"Schizoanalysis is Deleuze and Guattari's fusion of psychoanalytic-inspired theories of the self, the libido and desire with Marx-inspired theories of the economy, history and society. Schizoanalysis holds that art's function is both political and aesthetic - it changes perception. If one cannot change perception, then, one cannot change anything politically. This is why Deleuze and Guattari always insist that the artists operate at the level of the real (not the imaginary or the symbolic). Ultimately, they argue, there is no necessary distinction to be made between aesthetics and politics. One is simply the flipside of the other because both concern the formation and transformation of social and cultural norms. Deleuze and the Schizoanalysis of Visual Art explores how every artist, good or bad, contributes to the structure and nature of society because their work either reinforces social norms, or challenges them. On this view of things, we are all artists, we all have the potential to exercise what might be called a 'aesthetico-political function' and change the world around us; or, just as easily, we can dwell like assassins, and not only let the status quo endure but fight to preserve it as though it were freedom itself"--